ChemInform Abstract: Synthesis of Conformationally Restricted C2 Symmetric Macrodiolides via Head to Tail Dimerization of Carbonyl Ylides. Issue 16 (22nd April 2014) - Muthusamy, Sengodagounder; Sivaguru, Manickasamy
Abstract A simple procedure is developed for the synthesis of the title species via rhodium(II) carbenoid induced head to tail dimerization of carbonyl ylides having unactivated alkyne or alkene functionalities.